Carta de suelos de la República Argentina, partido de Villarino, provincia de Buenos Aires. Escala 1:250000 - Rodriguez, Dario Martin; Angelini, Marcos Esteban; Carreira, Daniel Antonio; Otero Estrada, Edit; Schulz, Guillermo; Tenti Vuegen, Leonardo Mauricio; Irigoin, Julieta; Pezzola, Nestor Alejandro; Winschel, Cristina Ines; Andreu, Roberto; Arcuri, julián; Rollie, Claudio; et al. (Instituto de Suelos, 2024)
Proyectos: PNSUELO 1134032 y PNSUELO 1134033.